Development of Low-Dielectric Modified Polyimide with Low-Temperature Radical Curing for High-Frequency Flexible Printed Circuit Boards - Seonwoo Kim; Suin Chae; Mirae Seo; Yubin Kim; Soobin Park; Sehoon Park; Hyunjin Nam (Micro, 2025)
This study presents the development of a modified polyimide (MPI) with low dielectric properties and low-temperature curing capability for high-frequency flexible printed circuit boards (FPCBs). MPI was cured using dicumyl peroxide (DCP) at 80–140 °C through a radical process optimized via DSC analysis, while Fourier-transform infrared (FT-IR) confirmed the elimination of C=C bonds and the formation of imide structures. The MPI film exhibited low dielectric constants (Dk) of 1.759 at 20 GHz and 1.734 at 28 GHz, with ultra-low dissipation factors (Df) of 0.00165 and 0.00157. High-frequency S-parameter evaluations showed an excellent performance, with S11 of −32.92 dB and S21 of approximately −1 dB. Mechanical reliability tests demonstrated a strong peel strength of 0.8–1.2 kgf/mm (IPC TM-650 2.4.8 standard) and stable electrical resistance during bending to ~6 mm radius, with full recovery after severe deformation. These results highlight MPI’s potential as a high-performance dielectric material for next-generation FPCBs, combining superior electrical performance, mechanical flexibility, and compatibility with low-temperature processing.